Memory properties and charge effect study in Si nanocrystals by scanning capacitance microscopy and spectroscopy - Lin, Zhen (Springer, 2011)
In this letter, isolated Si nanocrystal has been formed by dewetting process with a thin silicon dioxide layer on top. Scanning capacitance microscopy and spectroscopy were used to study the memory properties and charge effect in the Si nanocrystal in ambient temperature. The retention time of trapped charges injected by different direct current (DC) bias were evaluated and compared. By ramp process, strong hysteresis window was observed. The DC spectra curve shift direction and distance was observed differently for quantitative measurements. Holes or electrons can be separately injected into these Si-ncs and the capacitance changes caused by these trapped charges can be easily detected by scanning capacitance microscopy/spectroscopy at the nanometer scale. This study is very useful for nanocrystal charge trap memory application.